2018
DOI: 10.32607/20758251-2018-10-2-4-15
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and Cerebral Microangiopathy (Cerebral Small Vessel Disease): Genetic and Epigenetic Aspects of Their Relationship

Abstract: Hypertension (HT) and its cerebral complications are extremely vexing medical and social problems. Despite the obvious association between hypertension and the clinical and neuroimaging features of cerebral microangiopathy (CMA) (also known as cerebral small vessel disease), the causal links between them remain ambiguous. Besides, antihypertensive therapy as the only way to manage these patients does not always prevent brain damage. Knowledge about the key factors and mechanisms involved in HT and CMA developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 114 publications
0
4
0
Order By: Relevance
“…Lasso regression shows that gender difference is also important factors associated with CSVD [34], and men of the onset of CSVD contribution is much greater than women. The rise of a large number of studies have shown that estrogen levels might be in circulation system has a protective effect.…”
Section: Discussionmentioning
confidence: 97%
“…Lasso regression shows that gender difference is also important factors associated with CSVD [34], and men of the onset of CSVD contribution is much greater than women. The rise of a large number of studies have shown that estrogen levels might be in circulation system has a protective effect.…”
Section: Discussionmentioning
confidence: 97%
“…Additional analyses of time-of-flight MRI measurements would benefit future studies. Moreover, previous studies pointed out that hypertension and alterations in brain vasculature relate to myelin loss and M1 pathology (Jacków-Nowicka et al 2021; Tsushima, et al 2003; Dobrynina et al 2018, Li et al 2023; Schreiber et al 2023). Here, 9/17 older adults showed global signs of vascular health risk (i.e., presence of hypertension and/or signs of cerebral small vessel diseases outside S1 and M1).…”
Section: Discussionmentioning
confidence: 99%
“…The arterial hypertension perhaps is the prototype of pathologies in which the interaction between genes and the environment plays a major role in the genesis and maintenance of the high blood pressure values. At the same time, we are more and more delineating the interactive mechanisms in which the external environment is acting on the genome, modifying it, with consequent aging of the apparatuses and the onset of pathologies that are undermining the health of the organism [16]. Nothing prevents us from believing that the pathways of research, clinical and eminently gerontological, cannot overlap.…”
Section: Discussionmentioning
confidence: 99%